2015
DOI: 10.1016/j.cbi.2015.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 5 monoclonal antibodies for immunopurification of human butyrylcholinesterase on Dynabeads: KD values, binding pairs, and amino acid sequences

Abstract: Human butyrylcholinesterase (HuBChE) is a stoichiometric bioscavenger of nerve agents and organophosphorus pesticides. Mass spectrometry methods detect stable nerve agent adducts on the active site serine of HuBChE. The first step in sample preparation is immunopurification of HuBChE from plasma. Our goal was to identify monoclonal antibodies that could be used to immunopurify HuBChE on Dynabeads Protein G. Mouse anti-HuBChE monoclonal antibodies were obtained in the form of ascites fluid, dead hybridoma cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 25 publications
2
31
0
Order By: Relevance
“…7 The heavy and light chain nucleotides of B2 18-5 were sequenced, cloned into expression vectors, expressed in a stable Chinese hamster ovary cell line, and the antibody purified by Syd Labs, Natick, MA. 8 B2 18-5 efficiently immunopurifies HuBChE from plasma stored at 4 or −20 °C. 8 Antimouse IgG conjugated to horse radish peroxidase was from Cell Signaling, cat# 7076.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The heavy and light chain nucleotides of B2 18-5 were sequenced, cloned into expression vectors, expressed in a stable Chinese hamster ovary cell line, and the antibody purified by Syd Labs, Natick, MA. 8 B2 18-5 efficiently immunopurifies HuBChE from plasma stored at 4 or −20 °C. 8 Antimouse IgG conjugated to horse radish peroxidase was from Cell Signaling, cat# 7076.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…8 B2 18-5 efficiently immunopurifies HuBChE from plasma stored at 4 or −20 °C. 8 Antimouse IgG conjugated to horse radish peroxidase was from Cell Signaling, cat# 7076.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Similar to B2 18-5, monoclonal mAb2 has broad species specificity. Pairing analysis on the Octet Red96 system showed that mAb2 and B2 18-5 bind to overlapping but not identical epitopes on HuBChE [16]. B2 18-5 paired with mAb2 when B2 18-5 was the capture antibody, but not in the reverse format when mAb2 was the capture antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Use of these monoclonal antibodies for immunoextraction of BChE from human plasma is described in [16]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation